1965
DOI: 10.1002/pen.760050207
|View full text |Cite
|
Sign up to set email alerts
|

Polyimides—new high temperature polymers: H‐film, a polypyromellitimide film

Abstract: H‐Film is a polypyromellitimide which results from polycondensation of pyromellitic dianhydride and an aromatic diamine. Its unique blend of thermal, physical, and electrical properties make it an outstanding candidate for a variety of electrical and non‐electrical end‐use applications. These properties recommend H‐Film for use as Class H (220°C) electrical insulation. Thermal aging of this polymeric film to embrittlement in air will require on the order of ten years at 250°C (482°F), one year at 275°C (527°F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2004
2004

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The obtained values agree quite well with values reported in the literature. Traeger and Salazar [323] reported an activation energy of 163€20 kJ mol 1 for the pyrolysis of Kapton in air, while Heacock and Berr [324] published values between 162 and 165 kJ mol 1 . The same authors reported a two-step process with an activation energy of 232 kJ mol 1 for the thermal degradation of polyimide in helium.…”
Section: C) Refinement At Low Temperature-differences For Imide/aromamentioning
confidence: 98%
“…The obtained values agree quite well with values reported in the literature. Traeger and Salazar [323] reported an activation energy of 163€20 kJ mol 1 for the pyrolysis of Kapton in air, while Heacock and Berr [324] published values between 162 and 165 kJ mol 1 . The same authors reported a two-step process with an activation energy of 232 kJ mol 1 for the thermal degradation of polyimide in helium.…”
Section: C) Refinement At Low Temperature-differences For Imide/aromamentioning
confidence: 98%
“…The maximum decomposition temperature occurs at 546 °C, at which a primary scission process occurs at the imide bonds (C-N), followed by second cleavage (C-C) resulting in the elimination of C=0 groups. 25 The 46% weight loss of BCPI at 651 °C is thought to be the decomposition of imide structures and ketone groups of BCPI, the theoretical value of which is 35% weight loss.…”
Section: Resultsmentioning
confidence: 99%
“…in detail' 58 ' and it is claimed that it retains useful mechanical and electrical properties from cryogenic temperatures to beyond 500 °C. It does not melt or burn, has a zero strength temperature of above 800 °C and a useful life of 10 years in air at 250 °C is also claimed.…”
Section: Poly(aromatic-lmides)mentioning
confidence: 99%